Mechanism of Acrosome Biogenesis in Mammals - Khawar, Muhammad Babar; Gao, Hui; Li, Wei (Frontiers in Cell and Developmental Biology, 2019)
During sexual reproduction, two haploid gametes fuse to form the zygote, and the acrosome is essential to this fusion process (fertilization) in animals. The acrosome is a special kind of organelle with a cap-like structure that covers the anterior portion of the head of a the spermatozoon. The acrosome is derived from the Golgi apparatus and contains digestive enzymes. With the progress of our understanding underlying of acrosome biogenesis, a number of models have been proposed to address the origin of the acrosome. The acrosome has been regarded as a lysosome-related organelle, and it has been proposed to have originated from the lysosome or the autolysosome. Our review will provide a brief historical overview and highlight recent findings on acrosome biogenesis in mammals.